LA EMERGENCIA DE LA MIRADA SOCIOLÓGICA: ANÁLISIS SOCIOLÓGICO SOBRE LAS DIMENSIONES SOCIALES DE LAS IMÁGENES - Carballo Chaves, Pablo (2017)
In this document are presented three visual phenomena that had an impact on the Costa Rican society. The visual formats were: an international photograph, a local/national video, and finally, the phenomenon known as “selfie” or digital self-portrait. There are developed a series of ideas about sociological profiles in order to comprehend the relationships and stereotypes. But with the purpose of question them and suggest other comprehension methods, what we call, following a traditional sociological concept, the sociological imagination. One of the reached conclusions is that the convulsed and broken vision of the analyzing method causes that making a digital self-portrait is the way of not seeing one’s self implicated in the uncertainty. This document is also a pedagogical effort to approach the students and other readers to the sociological reflection, from the visual experience and possible assimilations.